Ukraine’s Trade Relations with the EU Countries - Yuliia Poliakova; Oksana Shayda; Nataliia Drebot; Mariana Myronova (Uniwersytet WSB Merito w Poznaniu, 2025)
The article presents an analysis of characteristics and prospects of Ukraine’s foreign trade with key trading partners in the EU. The authors examine the role of insti-tutional support, with emphasis on the liberalisation of mutual trade relations and the implementation of existing policy documents. In addition to analysing the dynamics and current structure of Ukraine’s foreign trade with the EU, the authors present an econo-metric model that illustrates the relationship between Ukraine’s GdP and the indicators of exports of goods to the EU and imports of goods from the EU for the period 2012–2023. The presented data indicate that higher exchange of goods with the EU had a positive impact on Ukraine’s economic growth. Taking into account current characteristics and problems of Ukraine’s foreign trade development in the context of global factors and Russia’s full-scale invasion, the authors identify potential opportunities for integration with European markets and the primacy of European collaboration in Ukraine’s foreign economic policy
Stosunki handlowe Ukrainy z krajami UE
Keywords: foreign trade; merchandise exports; merchandise imports; balance of trade; free-trade zone